(untitled) (Law and Safety, 2020)
Issues related to the assessment of the professionalism of police officers are inevitably intertwined with the increasing role of the moral foundations of their activities. The implementation of generally accepted rules of conduct, which are formed in the legal consciousness of the individual, reflects the level of his moral and legal thinking. In our context, the peculiarity of morality is that it is manifested not only in the content of the police, but also in the form of its implementation, playing the role of the most important factor in assessing the work of the police by society. Moral and psychological stability is considered as a determining factor of public confidence in the police. The author has singled out psychological structure of this characteristic, namely: motivational component, the indicators of which are a positive attitude to service, awareness of the importance of conscientious performance of official tasks and conscious desire to perform professional duties, belief in the value of moral norms and the need to subordinate own behavior; cognitive component, which includes knowledge of the legal basis of professional activity, ethical requirements of police officers’ behavior, the rules of use of physical force, special means and firearms; professional-personal component, which contains such professional moral and psychological qualities as professional honor, justice, decency, honesty, compassion and empathy, attitude to the rule of law, discipline, humanity, responsibility and a reflective component that characterizes the ability of a police officer to analyze phenomena of own consciousness and activity and assess the level of formation of moral and psychological stability, ability to effectively solve job problems. The reasons of the existing problems in realization of moral principles of professional activity of police officers are defined. The ways of formation of high moral and psychological stability of police officers, first of all, through departmental education are offered.